2013
DOI: 10.1056/nejmoa1303154
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Angiotensin Inhibition for the Treatment of Diabetic Nephropathy

Abstract: Combination therapy with angiotensin-converting-enzyme (ACE) inhibitors and angiotensin-receptor blockers (ARBs) decreases proteinuria; however, its safety and effect on the progression of kidney disease are uncertain. Methods We provided losartan (at a dose of 100 mg per day) to patients with type 2 diabetes, a urinary albumin-to-creatinine ratio (with albumin measured in milligrams and creatinine measured in grams) of at least 300, and an estimated glomerular filtration rate (GFR) of 30.0 to 89.9 ml per minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
599
2
26

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 997 publications
(663 citation statements)
references
References 17 publications
9
599
2
26
Order By: Relevance
“…On the other hand, whether such a combination may reduce intraglomerular pressure to an extent that could increase the risk for acute kidney injury events needs to be elucidated. In light of findings from the Ongoing Telmisartan Alone and in Combination With Ramipril Global Endpoint Trial (ONTARGET), Aliskiren Trial in Type 2 Diabetes Using Cardiovascular and Renal Disease Endpoints (ALTITUDE) and Veterans Affairs Nephropathy in Diabetes trial (VA-NEPHRON-D), which use strategies of dual RAAS blockade [8][9][10], this is an important consideration that requires further human physiological investigation and surveillance in ongoing clinical trials. Finally, our observations may have particular implications for primary renal preventive strategies in patients with type 1 diabetes, since RAAS blockade monotherapy is ineffective in normotensive, normoalbuminuric patients with preserved renal function.…”
Section: δP Fmentioning
confidence: 99%
“…On the other hand, whether such a combination may reduce intraglomerular pressure to an extent that could increase the risk for acute kidney injury events needs to be elucidated. In light of findings from the Ongoing Telmisartan Alone and in Combination With Ramipril Global Endpoint Trial (ONTARGET), Aliskiren Trial in Type 2 Diabetes Using Cardiovascular and Renal Disease Endpoints (ALTITUDE) and Veterans Affairs Nephropathy in Diabetes trial (VA-NEPHRON-D), which use strategies of dual RAAS blockade [8][9][10], this is an important consideration that requires further human physiological investigation and surveillance in ongoing clinical trials. Finally, our observations may have particular implications for primary renal preventive strategies in patients with type 1 diabetes, since RAAS blockade monotherapy is ineffective in normotensive, normoalbuminuric patients with preserved renal function.…”
Section: δP Fmentioning
confidence: 99%
“…Similar results were later found in the Aliskiren Trial in Type 2 Diabetes Using Cardio-Renal Endpoints (ALTITUDE) and the Veterans Affairs Nephropathy in Diabetes (VA NEPHRON-D) trials: findings showed no benefit with respect to mortality or CVEs and that intensive treatment with dual reninangiotensin-aldosterone system (RAAS) blockade even may even be harmful. The effects of BP lowering and/or RAAS blockade are therefore still under debate [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is underway to determine a possible role in prevention of diabetic nephropathy and cardiovascular disease CCR2; C-C chemokine receptor 2; CTGF, connective tissue growth factor; JAK, Janus kinase; MCP1, monocyte chemoattractant protein 1; NEP, neutral endopeptidase; Nrf2, nuclear factor (erythroid-derived 2)-like 2; SGLT2, sodium-glucose co-transporter 2; STAT, signal transducers and activators of transcription inhibitor and ARB therapy and with the addition of renin inhibitors or mineralocorticoid receptor antagonists to ACE inhibitors or ARBs (for example, see [17]). Recent research has uncovered new dimensions of the RAAS, including pathways that produce vasoactive angiotensins other than angiotensin II and perhaps an important role for the type 2 angiotensin receptor subtype in the transduction of signals leading to diabetic complications [10].…”
Section: Many Novel Agents Targeting Individual Pathways Leading To Dmentioning
confidence: 99%